Astaxanthin counteracts the effects of heat shock on the maturation of bovine oocytes - Ispada, J.; Rodrigues, T. A.; Risolia, P. H. B. [UNESP]; Lima, R. S. [UNESP]; Goncalves, D. R.; Rettori, D.; Nichi, M.; Feitosa, W. B.; Paula-Lopes, F. F. [UNESP] (Csiro Publishing, 2018)
The cellular mechanisms induced by elevated temperature on oocytes are not fully understood. However, there is evidence that some of the deleterious effects of heat shock are mediated by a heat-induced increase in reactive oxygen species (ROS). In this context, carotenoid antioxidants might have a thermoprotective effect. Therefore, the objective of this study was to determine the role of astaxanthin (AST) on oocyte ROS production and on the redox profile and developmental competency of cumulus-oocyte complexes (COCs) after 14 h heat shock (41 degrees C) during in vitro maturation (IVM). Exposure of oocytes to heat shock during IVM increased ROS and reduced the ability of the oocyte to cleave and develop to the blastocyst stage. However, 12.5 and 25nM astaxanthin rescued these negative effects of heat shock; astaxanthin counteracted the heat shock-induced increase in ROS and restored oocyte developmental competency. There was no effect of astaxanthin on maturation medium lipid peroxidation or on glutathione peroxidase and catalase activity in oocytes and cumulus cells. However, astaxanthin stimulated superoxide dismutase (SOD) activity in heatshocked cumulus cells. In conclusion, direct heat shock reduced oocyte competence, which was restored by astaxanthin, possibly through regulation of ROS and SOD activity in oocytes and COCs.
Keywords: antioxidant enzymes; cumulus cells; oxidative stress; temperature